Role of hyperglycemia in the pathogenesis of Na+/K+ disturbance - Parmar, Kumari Shipra; Singh, Samir; Singh, Ganesh Kumar (International Journal of Research in Medical Sciences, 2016)
Background: Electrolytes play an important role in maintaining acid-base balance, blood-clotting, control body fluid, muscle contraction, nerve conduction. The diabetic patients develop frequently a constellation of electrolyte imbalance. Imbalance in electrolyte concentration may affect the course of diabetes and its management. It has been reported that there is an inverse relationship between serum sodium (Na+) and potassium (K+) levels in diabetic patients. The aim of present study was to determine whether such relation is seen in context of Nepal and whether this inverse relation depends upon serum glucose levels in diabetic patients for their glycemic control. Methods: This is a retrospective study performed on records of 135 diabetic patients who were treated at out-patient clinic of Kist Medical College and Teaching Hospital from 15 June 2015-15 July 2015. Fasting blood glucose (FPG) level was analyzed with semiautomatic analyzer- humalyzer 3000 by GOD-POD method and Na+ and K+ levels were analyzed with ion selective electrode- nova electrolyte. The relationship among serum Na+ level, serum K+ levels and Fasting plasma glucose levels were determined by SPSS version 20. Results: Serum Na+ level was insignificantly negatively correlated (r=-0.091, p=0.296) with FPG level while a positive correlation of serum K+ level (r=0.235, p=0.006) was seen with FPG level and an inverse relation between serum Na+ and K+ was found. Age showed insignificant negative correlation with serum Na+ (r= -0.203, p=0.018), insignificant positive correlation with K+ (r=0.067, p=0.443) and insignificant negative correlation with FPG (r= -0.045, p=0.608). Conclusions: Hyperglycemia disrupts the balance of serum Na+ and K+ in uncontrolled diabetes mellitus.